Do patient surveys work? The influence of a national survey programme on local quality-improvement initiatives. Issue 6 (8th December 2008) - Reeves, R; Seccombe, I
Abstract : Objectives: To assess current attitudes towards the national patient survey programme in England, establish the extent to which survey results are used and identify barriers and incentives for using them. Design: Qualitative interviews with hospital staff responsible for implementing the patient surveys (survey leads). Setting: National Health Service (NHS) hospital organisations (trusts) in England. Participants: Twenty-four patient survey leads for NHS trusts. Results: Perceptions of the patient surveys were mainly positive and were reported to be improving. Interviewees welcomed the surveys' regular repetition and thought the questionnaires, survey methods and reporting of results, particularly inter-organisational benchmark charts, were of a good standard. The survey results were widely used in action planning and were thought to support organisational patient-centredness. There was variation in the extent to which trusts disseminated survey findings to patients, the public, staff and their board members. The most common barrier to using results was difficulty engaging clinicians because survey findings were not sufficiently specific to specialties, departments or wards. Limited statistical expertise and concerns that the surveys only covered a short time frame also contributed to some scepticism. Other perceived barriers included a lack of knowledge of effective interventions, and limited time and resources. Actual and potential incentives for using survey findings included giving the results higher weightings in the performance management system, financial targets, Payment by Results (PbR), Patient Choice, a patient-centred culture, leadership by senior members of the organisation, and boosting staff morale by disseminating positive survey findings. Conclusion: The national patient surveys are viewed positively, their repetition being an important factor in their success. The results could be used more effectively if they were more specific to smaller units.